Review of Acute Orthopedic Injuries - Kathryn Miner; Hans House (Association of American Medical Colleges, 2011)
Abstract This resource is a PowerPoint slide bank of 45 brief cases of acute orthopedic injuries. It includes X-ray images of fractures and clinical case information. This resource is intended as a broad review of muscle-skeletal X-ray reading. The presentation has been used on three previous occasions in the University of Iowa emergency medicine residency, to an audience of residents and medical students. Evaluations of the presentation are very strong. It received Likert scores of 5 out of 5 on effectiveness of format, usefulness of content, and relevance to practice. One hundred percent of responders reported that the presentation would likely change their practice in some way. This program has since been adopted as a standard learning session for new first-year residents during their orientation course.